Intangible Investment and the Swedish Manufacturing and Service Sector Paradox - Harald Edquist (Research Institute of Industrial Economics (IFN), 2011)
Since the mid 1990s labor productivity growth in Sweden has been high compared to Japan, the US and the western EU-countries. While productivity growth has been rapid in manufacturing, it has been much slower in the service sector. Paradoxically, all employment growth since the mid 1990s has been created in business services. The two traditional explanations of this pattern are Baumols disease and outsourcing. This paper puts forward an additional explanation, based on the observation that manufacturing industries have invested heavily in intangible assets such as R&D and vocational training. In 20052006, intangible investment was 25 percent of value added in manufacturing, while the corresponding figure for the service sector was 11 percent. Moreover, calculations based on the growth accounting framework at the industry level in 20002006 show that intangible investment accounted for almost 30 percent of labor productivity growth in manufacturing. Thus, investments in intangibles that mostly are knowledge intensive services have contributed considerable to productivity growth in Swedish manufacturing since 1995.
Keywords: O14; O32; O33; 330; Intangibles; Manufacturing; Productivity growth; Service sector; Sector analysis; Investition; Immaterielle Güter; Immaterielle Werte; Arbeitsproduktivität; Verarbeitendes Gewerbe; Dienstleistungssektor; Schweden